Resource Boom and Fiscal Dependence in an Archipelagic Province: Evidence from North Maluku, Indonesia - Adam, Mukhtar; Nurwanah, Andi (Amkop Management Accounting Review (AMAR), 2025)
This study aims to identify and interpret the paradox between exports, GRDP, and fiscal capacity in island provinces, which has not been widely researched in Indonesian fiscal literature. This study uses a quantitative descriptive analysis approach based on official secondary data, including the North Maluku Provincial Economic Report (Bank Indonesia, August 2025 edition) and the Regional Fiscal Review (KFR) for the first quarter of 2025 (Ministry of Finance). All data were analyzed at the quarterly level (Q1–Q2 2025) and compared with national economic performance to provide a comparative context. This study found several findings. First, North Maluku's economic growth in 2025 confirms the central role of nickel downstreaming as the driving force behind the GRDP. Economic dependence on the mining and manufacturing sectors dominates the economic structure, shifting the contribution of the agricultural industry and the role of domestic consumption. Second, a comparative analysis between exports and GRDP reveals structural imbalances. The phenomenon of exports exceeding GRDP indicates a very high level of economic openness as well as excessive dependence on global markets. Third, the gap becomes even more apparent when comparing exports with regional fiscal capacity. This fact confirms that, despite North Maluku being the center of Indonesia's nickel exports, the budgetary benefits received by the region are minimal. These findings support Lewis' (2023) criticism of Indonesia's weak fiscal decentralization, as well as the conclusions from Ahmad et al. (2024) that island provinces receive a smaller share of transfers due to a land-biased formula. Fourth, high logistics costs, market fragmentation between islands, and the concentration of growth in large industrial areas have widened the gap between regions. Small islands continue to face high prices for necessities and limited fiscal capacity, despite collectively recording large export surpluses. The results of this study confirm that North Maluku faces a double paradox: it is an “export giant” but “fiscally weak.” Spectacular economic growth due to nickel downstreaming has not translated into fiscal independence and inclusive prosperity. Therefore, there is a need for national fiscal policy reforms that are more equitable for the islands, an increase in the share of mining revenue, diversification of the local revenue base, and downstreaming policies that are more integrated with local socio-economic needs. Without these measures, North Maluku risks being trapped in an island version of the resource curse.